Compliance with Immunization Against H1N1 Influenza Virus Among Children with Cancer. (14th February 2013) - Doganis, Dimitrios; Tsolia, Maria; Dana, Helen; Bouhoutsou, Despina; Pourtsidis, Apostolos; Baka, Margarita; Varvoutsi, Maria; Servitzoglou, Marina; Kosmidis, Helen
<x xml:space="preserve">Abstract</x> In this report, we describe the experience with immunization against pandemic influenza A H1N1 in children with cancer treated at a pediatric oncology department during the pandemic season (2009). According to the guidelines, vaccination of all children with cancer receiving chemotherapy as well as those who had completed treatment was scheduled. Among the 140 children who were eligible for immunization, 122 were immunized, achieving a compliance rate of 87% despite negative publicity and low vaccine uptake in the general population. The vaccine was tolerated and none of the vaccinated children developed influenza. It is concluded that high immunization rates can be achieved among pediatric oncology patients.